Mining oomycete proteomes for metalloproteases leads to identification of candidate virulence factors in Phytophthora infestans - Schoina, Charikleia (John Wiley and Sons Inc., 2021)

(untitled) (Mol Plant Pathol)
Pathogens deploy a wide range of pathogenicity factors, including a plethora of proteases, to modify host tissue or manipulate host defences. Metalloproteases (MPs) have been implicated in virulence in several animal and plant pathogens. Here we investigated the repertoire of MPs in 46 stramenopile species including 37 oomycetes, 5 diatoms, and 4 brown algae. Screening their complete proteomes using hidden Markov models (HMMs) trained for MP detection resulted in over 4,000 MPs, with most species having between 65 and 100 putative MPs. Classification in clans and families according to the MEROPS database showed a highly diverse MP repertoire in each species. Analyses of domain composition, orthologous groups, distribution, and abundance within the stramenopile lineage revealed a few oomycete‐specific MPs and MPs potentially related to lifestyle. In‐depth analyses of MPs in the plant pathogen Phytophthora infestans revealed 91 MPs, divided over 21 protein families, including 25 MPs with a predicted signal peptide or signal anchor. Expression profiling showed different patterns of MP gene expression during pre‐infection and infection stages. When expressed in leaves of Nicotiana benthamiana, 12 MPs changed the sizes of lesions caused by inoculation with P. infestans; with 9 MPs the lesions were larger, suggesting a positive effect on the virulence of P. infestans, while 3 MPs had a negative effect, resulting in smaller lesions. To the best of our knowledge, this is the first systematic inventory of MPs in oomycetes and the first study pinpointing MPs as potential pathogenicity factors in Phytophthora.